Sonographic Relation between Adnexal Masses and Endometrial Thickness in Infertile Females with Hormonal Imbalance: Infertility - Yousaf Farooq, Syed Muhammad; Gilani, Syed Amir; Tul Sughra, Syeda Khadija; Iqbal, Amjad; ., Mahjabeen; Abidin, Syed Zain ul; Jallad, Lina Khaled (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the sonographic relation between adnexal masses and endometrial thickness in infertile females with hormonal imbalances. Study Design: Cross-sectional analytical study. Place and Duration of Study: Department of Radiology, Gilani Ultrasound Center, Jamiat Hospital & Green Town Clinic, Lahore Pakistan, from Mar 2019 to Jan 2020. Methodology: In this study, 150 infertile females with adnexal masses, aged 18 to 45, were included. Data were collected according to the age, adnexal masses, endometrium thickness, and type of infertility hormonal levels. The endometrium thickness was measured in the sagittal plane at the thickest echogenic area from one basal endometrial interface across the endometrial canal to the other basal surface. Results: The mean age was 32.55±6.33 years. Out of 150 patients, 97 patients with abnormal and 53 were with normal hormonal levels. Follicular cysts (33%), Polycystic ovarian syndrome (29.9%) and 23.7% hemorrhagic cysts were found with abnormal hormonal levels. Conclusion: There was a significant correlation between adnexal masses and endometrial thickness in infertile females with abnormal hormonal levels.